2019
DOI: 10.1108/ijwbr-03-2018-0010
|View full text |Cite
|
Sign up to set email alerts
|

Clustering Spanish alcoholic beverage shoppers to focus marketing strategies

Abstract: Purpose The purpose of this study is twofold: to analyse the influence of both individual and environmental factors in order to explain alcoholic spending and to identify different groups of alcoholic beverage shoppers. Design/methodology/approach For the research, an online questionnaire was distributed among 1,023 Spanish participants of age more than 18 years. Multivariance techniques were used for analysis, and the results show significant influence of specific motivational domains, brand awareness, perc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Prior research on brand love and purchase loyalty has enhanced knowledge of both hedonic and functional products in individual countries (Carroll and Ahuvia, 2006; Bruwer and Alant, 2009). Similarly, previous research on wine marketing and branding across cultures and markets advanced theory and practice (Johnson and Bruwer, 2007; Cohen et al , 2009; Mueller et al , 2011; Drennan, et al , 2015; Velikova et al , 2015; Hernández et al , 2019). To the authors’ knowledge, however, this study is one of few comparing hedonic product consumption in an economically developed and emerging country with differing cultural consumer-relationships for a spirit (tequila).…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Prior research on brand love and purchase loyalty has enhanced knowledge of both hedonic and functional products in individual countries (Carroll and Ahuvia, 2006; Bruwer and Alant, 2009). Similarly, previous research on wine marketing and branding across cultures and markets advanced theory and practice (Johnson and Bruwer, 2007; Cohen et al , 2009; Mueller et al , 2011; Drennan, et al , 2015; Velikova et al , 2015; Hernández et al , 2019). To the authors’ knowledge, however, this study is one of few comparing hedonic product consumption in an economically developed and emerging country with differing cultural consumer-relationships for a spirit (tequila).…”
Section: Discussionmentioning
confidence: 77%
“…Considering the purchase of hedonic products such as wine or cognac, the research found that brand was the most important factor influencing consumers’ choice (Lockshin et al , 2009; Drennan et al , 2015). While the study of wine branding and marketing has matured significantly (Ellis and Caruana, 2018), there is a paucity of research examining consumer-brand relationships across multiple nations in other alcohol products, such as tequila [1] (Hernández et al , 2019; Wei et al , 2019). Furthermore, tequila is an appropriate product to study as its recent sales growth has outpaced that of other spirits categories (Monllos, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The packaging is one of the most powerful tools in food industry as it acts also as a communication and branding medium beside its traditional role. As a marketing tool the packaging can promote a healthier lifestyle and change by itself the consumer habits [ 7 , 8 , 9 , 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%